2020
DOI: 10.1371/journal.ppat.1008702
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting distinct proteolytic activities of FMDV Lpro implicates cleavage and degradation of RLR signaling proteins, not its deISGylase/DUB activity, in type I interferon suppression

Abstract: The type I interferon response is an important innate antiviral pathway. Recognition of viral RNA by RIG-I-like receptors (RLRs) activates a signaling cascade that leads to type I interferon (IFN-α/β) gene transcription. Multiple proteins in this signaling pathway (e.g. RIG-I, MDA5, MAVS, TBK1, IRF3) are regulated by (de)ubiquitination events. Most viruses have evolved mechanisms to counter this antiviral response. The leader protease (L pro) of footand-mouth-disease virus (FMDV) has been recognized to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 98 publications
(168 reference statements)
2
26
0
Order By: Relevance
“…The viruses infect and damage the cells that express IL-2, IL-12, IL-15, IL-18, and IFNs which are required for NK cells activation. L pro blocks the activation of RLR pathway and inhibits the expression of various cytokines (89,90). Meanwhile, L pro cleaves eIF4G which also decreases the expression of IFNs and cytokines.…”
Section: Macrophages- Nk Cells- and Dcs-related Innate Immune Dysfunctionmentioning
confidence: 99%
“…The viruses infect and damage the cells that express IL-2, IL-12, IL-15, IL-18, and IFNs which are required for NK cells activation. L pro blocks the activation of RLR pathway and inhibits the expression of various cytokines (89,90). Meanwhile, L pro cleaves eIF4G which also decreases the expression of IFNs and cytokines.…”
Section: Macrophages- Nk Cells- and Dcs-related Innate Immune Dysfunctionmentioning
confidence: 99%
“…Two other genes that are part of the cellular ISGylation machinery, the ubiquitin-like protein modifier ISG15 and the ubiquitin specific peptidase USP18, were also upregulated in response to PEGpoIFNα. It has recently been demonstrated that FMDV actively induces protein deISGylation ( Medina et al, 2020a ; Visser et al, 2020 ). Furthermore, overexpression of ISG15 and the ISGylation machinery results in moderate inhibition of FMDV replication in porcine cells ( Medina et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant proteins of this pathway (RIG‐I, MAVS, TBK1, IRF‐3) are regulated by ubiquitin‐dependent modifications. In this respect, the TBKI kinase, responsible for phosphorylation of the transcription factor IRF3 is also cleaved by L pro in FMDV‐infected cells (Visser et al, 2020) at a KKLK site, resembling the minimal motif defined in Daxx and Gemin5 (Figure 2c). Interestingly, the mutations in L pro that impaired the reduction of IFN‐β mRNA levels displayed cleavage defects and/or degradation of the signaling proteins MAVS, TBK1, and NF‐κB p65, establishing a direct link between L pro activity and IFN reduction.…”
Section: Lpro Impact In Rna‐mediated Pathways Involved In Antiviral Defensementioning
confidence: 99%
“…Interestingly, the mutations in L pro that impaired the reduction of IFN-β mRNA levels displayed cleavage defects and/or degradation of the signaling proteins MAVS, TBK1, and NF-κB p65, establishing a direct link between L pro activity and IFN reduction. Thus, L pro 's ability to cleave RLR signaling proteins but not its deubiquitination/deISGylation activity correlates with suppressing IFN-α/β gene transcription (Medina et al, 2020;Visser et al, 2020).…”
Section: P R O Impact In Rna-mediated Pathways Involved In Antivimentioning
confidence: 99%